Modified reduced-volume intensity-modulated radiation therapy in non-metastatic nasopharyngeal carcinoma: A prospective observation series. (March 2021) - Guo, Qiaojuan; Zheng, Yahan; Lin, Jinyong; Xu, Yun; Hu, Cairong; Zong, Jingfeng; Lu, Tianzhu; Xu, Hanchuan; Chen, Bijuan; Liang, Qiandong; Xiao, Youping; Pan, Jianji; et al.
Highlights: "Modified reduced-volume IMRT" was re-defined based on our previous reported technique "reduced-volume IMRT". "Modified reduced-volume IMRT" omitted CTV1 and narrowed the margin of CTV2. This de-intensification technique was feasible and did not compromise therapeutic efficacy. This renew technique simplified the procedures of target contouring and optimization of RT plan. Abstract: Background and purpose: Although the efficacy of "reduced-volume intensity-modulated radiation therapy (IMRT)" in nasopharyngeal carcinoma (NPC) has been confirmed, two issues regarding the necessity of clinical target volume 1(CTV1) delineation and the optimal margin of CTV2 remained undetermined. The current series, utilized de-intensification technique that omitted the contouring of CTV1 and narrowed the margin of CTV2 from 10 mm to 8 mm, namely "modified reduced-volume IMRT" was initiated to evaluate the efficacy and feasibility of this renew technique in a prospective series. Patients and materials: Dosimetric analysis was performed in 40 non-metastatic NPC cases to evaluate whether our modification is feasible. Then this de-intensification technique was applied in non-metastatic NPC patients treated in our attending group since late 2014. Survival outcomes focused on local recurrence-free survival (LRFS) and local failure pattern were analyzed. Results: Preliminary dosimetric evaluation of "modified reduced-volume IMRT" showed that the 60 Gy isodose curve generated naturally by this technique could well wrap the target area of CTV1. Subsequent observation series, which included a total of 471 patients and had a median follow-up time of 46.2 months(range, 3.7–70.8 months), reported that 4-year estimated LRFS, regional recurrence-free survival (RRFS), distant metastasis-free survival (DMFS) and overall survival (OS) were 96.6%, 97.7%, 87.7% and 92.4%, respectively. All local recurrence lesions occurred within 95% isodose lines and were considered in-field failures. Conclusions: Our de-intensification technique "modified reduced-volume IMRT" was feasible and did not compromise therapeutic efficacy, well-designed multicenter prospective trials are needed for further research.